Crop-Livestock Integration in Farming System at Irrigation Area Case Study: Grobogan District, Central Java - Prasetyo, Teguh; Setiani, Cahyati; Kartaatmaja, Sunendar (Indonesian Animal Sciences Society, 2002)
Most of farmers in Central Java hold land about 0.25 â 0.3 ha. If they are only doing farming system with rice-rice-corn cropping pattern, their income per season will range from Rp 446.800 to Rp 586.000. Of course such earnings is not enough and unsuitable, so its necessary to find out some efforts for increasing farmers income. One of some alternative efforts can be carried out is diversification, i.e. developing farm enterprise which integrated with livestock. Related with that idea, we have been studying crop livestock integration in Grobogan District since November 2000. This study was carried out in order to find alternative sharing farm operation model on irrigation area which executed in group. The farmers included in this study are 454 farmers which posses land about 106.2 hectare, while livestock they breed are 180 cows for applicant in five units of stall together. Business management was carried out by one management which organized by group managers, includes farm enterprise (input, irrigation, integrated pest management, mechanic service, and marketing), livestock (input, IB service, animal health, straw treatment and selling the product), and also save-debt of money. The technology which introduced includes processing plant product technology, livestock breeding, and straw treatment for food and also ecreement of livestock for organic fertilizer. Along the production process both exertion can give input each other (internal input) by using by product and also can minimalize input from outside (low external input). Straw production of corn and rice plant which used for live stock woof are 3600 kg/ha and 4600 kg/ha respectly, meanwhile organic fertilizer that produced after 10 months observation was 216,8 tons. If the dosis of the fertilizer for rice plant/corn is 2 t/ha, so it can be used for rice plant and corn on 108.4 ha area. Up until 10 month observation, 4 calves were born and 17 catle were pregnant. Â Key words: Irrigation area, crop-livestock, beef cattle, rice, corn